2023
DOI: 10.1186/s13047-023-00603-5
|View full text |Cite
|
Sign up to set email alerts
|

Describing the factors related to rural podiatry work and retention in the podiatry workforce: a national survey

Abstract: Background Maldistribution of podiatrists limits capacity to address the footcare needs of the population. Understanding factors that impact recruitment and retention of Australian podiatrists is a key solution. The primary aim of this study was to describe factors related to rural podiatry work, and overall professional retention amongst Australian podiatrists. Methods We used data collected from the most recent relevant response of a cohort of Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Approval for PAIGE was provided by the Monash University Human Research Ethics Committee (7871). Details of the PAIGE study methods are published in detail elsewhere [15]. We used the CHERRIES (Checklist for Reporting Results of Internet E-Surveys) to guide collected data reporting [16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approval for PAIGE was provided by the Monash University Human Research Ethics Committee (7871). Details of the PAIGE study methods are published in detail elsewhere [15]. We used the CHERRIES (Checklist for Reporting Results of Internet E-Surveys) to guide collected data reporting [16].…”
Section: Methodsmentioning
confidence: 99%
“…The PAIGE survey questions were based on the Medicine in Australia: Balancing Employment and Life (MABEL) study [18]. Data were collected as per the PAIGE study methodology [19] and details related to data domains collected in each wave are published elsewhere [15]. Wave 1 survey is provided as Supplementary File 1.…”
Section: Data Collectionmentioning
confidence: 99%
“…The PAIGE survey questions were based on the Medicine in Australia: Balancing Employment and Life (MABEL) study [18]. Data were collected as per the PAIGE study methodology [19] and details related to data domains collected in each wave are published elsewhere [15]. Wave 1 survey is provided as Supplementary File 1.…”
Section: Data Collectionmentioning
confidence: 99%
“…In contrast, podiatrists who are contracted typically work as sole traders and are responsible for making their own contributions to a superannuation scheme [6], and do not always have access to leave entitlements. A recent study of Australian podiatrists identified that 16% (180 of 1,129) work in these contracted arrangements and 51% (573 of 1,129) are salaried employees [7].…”
Section: Introductionmentioning
confidence: 99%
“…Burnout remains a common problem affecting podiatrists. A recent survey focusing on Australian podiatrists found that 35% of respondents experienced burnout, which was associated with an intention to leave the profession [ 5 ].…”
Section: Introductionmentioning
confidence: 99%